Altered Spontaneous Glutamatergic and GABAergic Activity in the Peritumoral Cortex of Low-Grade Gliomas Presenting With History of Seizures - Dey, Soumil; Doddamani, Ramesh Sharanappa; Banerjee Dixit, Aparna; Tripathi, Manjari; Sharma, Meher Chand; Chandra, P. Sarat; Banerjee, Jyotirmoy (Frontiers in Neuroscience, 2021)
Peritumoral regions of WHO grade II gliomas, like astrocytoma and oligodendroglioma, have been reported to show epileptiform activities. Imbalance of glutamatergic and GABAergic mechanisms are primarily responsible for generation of these epileptiform activities. Here, we have compared the electrophysiological properties of pyramidal neurons in the intraoperative peritumoral specimens obtained from the glioma patients with (GS) and without (GN) history of seizures at presentation. Histology and immunohistochemistry were performed to assess infiltration of proliferating cells at the peritumoral tissues. Whole-cell patch clamp technique was performed to measure the spontaneous glutamatergic and GABAergic activity on to pyramidal neurons in the peritumoral samples of patients with GS (n=11) and GN (n=15). The cytoarchitecture of the peritumoral tissues were devoid of Ki67 immuno-positive cells. We observed higher frequency of spontaneous glutamatergic and GABAergic activities onto pyramidal neurons of peritumoral samples of patients with GS. Our findings suggest that, in spite of similar histopathological features, pyramidal neurons in peritumoral samples of patients with GS and GN showed differences in the spontaneous excitatory and inhibitory synaptic neurotransmission. Alteration in postsynaptic currents may contribute to the spontaneous epileptiform activity in patients with GS.